2005
DOI: 10.1515/secm.2005.12.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Elastic Stress Analysis in a Thermoplastic Composite Disc

Abstract: This study deals with thermo-elastic stress analysis on a thermoplastic composite disc reinforced curvilinearly with Ε-glass fibers. Its mechanical properties are obtained by using an Instron testing machine. The modulus of elasticity in the tangential direction is measured by using strain gauges due to the fitting of a solid disc into the composite disc. An analytical method is performed to determine thermal stresses for both uniform and linearly changing temperatures. The magnitude of the tangential stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Alexandrova and Vila Real [27] presented a mathematical model for displacement and stress fields in elastic-perfectly plastic anisotropic annular disks. Sayer et al [28] performed thermoelastic stress analysis on a thermoplastic curvilinearly fiberreinforced composite disk. They found that disks under linearly changing temperature produce lower stresses than under uniform temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexandrova and Vila Real [27] presented a mathematical model for displacement and stress fields in elastic-perfectly plastic anisotropic annular disks. Sayer et al [28] performed thermoelastic stress analysis on a thermoplastic curvilinearly fiberreinforced composite disk. They found that disks under linearly changing temperature produce lower stresses than under uniform temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The angular velocity of the disk is assumed to be, xðtÞ ¼ x 0 e Àkt , where x 0 and k are two constant parameters [7]. Employing the method of separation of variables, the displacement field is represented as u r ðr; tÞ ¼ R r ðrÞK r ðtÞ (27) u h ðr; tÞ ¼ R h ðrÞK h ðtÞ (28) where K r ðtÞ ¼ e À2kt , K h ðtÞ ¼ e Àkt , and R r ðrÞ and R h ðrÞ are two unknown functions of the radial coordinate, r, to be determined. Substituting Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that, thermal stresses occurred in the composite disc for the uniform thermal distribution due to the different thermal expansion coefficients in principal material directions. Sayer et al [10] studied thermo-elastic stress analysis on a low-density thermoplastic composite disc reinforced curvilinearly with E-glass fibers. Sayman [11] examined a thermal stress analysis on an aluminum metal-matrix orthotropic composite hollow disc by using an analytical solution.…”
Section: Introductionmentioning
confidence: 99%
“…The solution was performed numerically, for non-hardening case. Sayer et al [11] investigated thermo-elastic stresses on a low-density thermoplastic composite disc reinforced curvilinearly with E-glass fibres.…”
Section: Introductionmentioning
confidence: 99%